The influence of transformational leadership and servant leadership on employee performance mediated by job satisfaction - Putri, Rizki Wahyuni; Saputra, Pramana; Rosnani, Titik; Irdhayanti, Efa (Junal Ilmu Manajemen, 2025)
This study aims to analyze the effect of transformational leadership and servant leadership on employee performance, with job satisfaction as a mediating variable. Transformational leadership is known for its ability to inspire and motivate employees to achieve organizational goals more effectively through self-development and stronger commitment. On the other hand, servant leadership emphasizes the well-being and needs of employees, which creates a supportive and empathetic work environment. Both leadership styles have the potential to increase job satisfaction, which then has a positive impact on employee performance. In the context of public organizations, particularly the Dinas Perhubungan Kota Pontianak, an understanding of leadership and work ethics is essential to improve employee performance. This study used SmartPLS version 4 as a statistical tool and Structural Equation Modeling (SEM) as a data analysis method to test the hypothesis. The population in this study were 119 employees with sampling techniques using simple random sampling and resulted in 92 respondents being sampled in this study. The results showed that transformational leadership had no significant effect on employee performance. However, servant leadership has a positive and significant impact on employee work habits. In addition, job satisfaction can have a significant impact on employee performance. In addition, job satisfaction serves as a mediation between servant leadership, transformational leadership, and employee performance.